Sero-prevalence of Transfusion Transmissible Infections Markers Among Blood Donors Attending the Blood Transfusion Department Of A Teaching Hospital in Chittagong (Bangladesh Medical Journal, 2014)
As per Safe Blood Transfusion Law 2002 of Bangladesh and worldwide strategy of screening of Transfusion Transmissible Infections (TTIs) markers in blood donors of various categories is a must for the prevention of Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS), Hepatitis B virus (HBV), Hepatitis C virus (HCV), Syphilis and Malaria with a aim to decrease morbidity and mortality of the patients receiving blood and blood components. A total of 33,553 blood donors attending the Blood Transfusion Department of Chittagong Medical College Hospital from January 2009 to December 2009 amongst which replacement or relative donors were 30868 (92%), voluntary donors 2685 (8%) and male donors 27722 (82.62%), female donors 5831 (17.38%). Among the donors 15133 (45.10%), were of age group between 18-25 years, 17809 (53.08%) were of age group between 26-45 years, and 611 (1.82%) were of age group between 46-60 years. The purpose of this study was to determine the sero-prevalence of HIV, HBV, HCV, Syphilis and Malaria in blood donors in a Teaching Hospital at Chittagong, Bangladesh. Blood samples from selected donors were tested for HIV, HBV HCV and Malaria by Immunochromatographic (ICT) rapid test device, Syphilis by rapid plasma reagin (RPR) test device method. Screening procedures were in accordance with the manufacturers instruction in terms of adding serum, adding buffer and time duration of reading results. Screening result after compilation shows HIV was reactive in 7 (0.02%) donors all of which were male. HBV was reactive in 285 (0.849%) donors, out of which 272 (95.43%) were male and 13 (4.57%) were female. HCV was reactive in 23 (0.068%) donors, out of which 18 (78.24%) was male and 5 (21.76%) were female. Syphilis was reactive in 32 (0.095%) donors, out of which 29 (90.62%) was male and 3 (9.38%) were female. Malaria was reactive in 31(0.09%) donors all of which were male. By studing this prevalence, attention will be drawn towards severity of the situation so that effective measure can be taken to prevent further transmission of TTIs by blood transfusion. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18673 Bangladesh Medical Journal 2011 Vol.40(3):37-39